Determinan Penggunaan E-Wallet dengan Pendekatan Unified Theory of Acceptance and Use of Technology (UTAUT) - Safitri, Fibriani Ayu; Sari, Shinta Permata (Journal of Management and Bussines (JOMB), 2024)
This study aims to examine the influence of performance expectancy, effort expectancy, and social influence on behavioral intention, as well as the influence of facilitating conditions and behavioral intention on use behavior of e-wallet. The research method used is a quantitative approach with the use of a questionnaire distributed to 275 respondents to obtain more accurate data analysis results. Data analysis is conducted using Smart-PLS (Partial Least Squares) through testing the outer model, inner model, and hypothesis testing. The results show that performance expectancy, effort expectancy, and social influence have an effect on behavioral intention, as well as facilitating conditions and behavioral intention affecting use behavior. In conclusion, based on the existing determinant variables, all of them have an influence on the intention and use of e-wallets as digital payment technology. Keywords: Keywords: Behavioral Intention, Digital Payment, E-Wallet, Use Behavior, UTAUT